UJI IRITASI DAN AKTIVITAS TABIR SURYA SECARA IN VITRO MINYAK BIJI PALA DALAM SISTEM MIKROEMULSI DENGAN VARIASI TWEEN 80-ETANOL - Sri Eka Rahmadany; Aza Zakiyatun Nida; Risha Fillah Fithria; Ayu Shabrina (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
Nutmeg oil contains of α-pinene that can be used as sunscreen but it is thermolable. It is necessary to form a microemulsion system for nutmeg oil. This study was to determine in vitro SPF value by and irritation index from nutmeg oil in microemulsion system with Tween 80-ethanol as surfactant and cosurfactant. The system were made with 6.4 % of nutmeg oil and Tween 80-ethanol as with concentrations of 45% (F1), 50% (F2), 55% (F3). The nutmeg oil microemulsion was determined SPF value using spectrophotometer UV. The irritation test was done by the patch test method on rabbit skin with 4 groups of negative control, F1, F2, and F3. The skin was observed at 24, 48 and 72 hours. Quantitative data were analyzed using one way Anova while irritation test data were described descriptively. The results of the sunscreen activity on nutmeg oil microemulsion for F1, F2 and F3 were 8,9 ± 0,12; 9,2 ± 0,51; and 9,3 ± 0,32 (p > 0,05). This SPF value were categorized in maximum protection. The primary irritation index values for F1, F2 and F3 were 0,1±1; 0,3±2,5; 0,1±0; so it can be concluded that microemulsion of nutmeg oil were very mildly irritating.